Inuit Economic Responses to Euro‑American Contacts: Southeast Baffin Island, 1824‑1940 - Goldring, Philip (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1986)
AbstractFirst contacts between Inuit and European whalers on Cumberland Peninsula led to considerable movement of population after 1824. Whaling vessels aided the mobility of hunting groups and developed seasonal employment patterns. They also changed the material culture of Inuit hunting and the seasonal pattern of exploitation of marine mammals. Depletion of bowhead whales in the 1870s led the Inuit to diversify their hunting for trade, and diminished the number of whalers permanently living or seasonally visiting the region. The decline in ship-winterings increased the importance of permanent whaling stations as sources of ammunition and provisions. Collapse of the whaling industry and the outbreak of the First World War left most stations, including several new ones, under native management on behalf of British traders. In the 1920s the new Hudson's Bay Company post at Pangnirtung squeezed out less-efficient competition, concentrated on the white fox as the new fur staple, and reorganized production through small hunting camps. This paper examines the manner in which the Inuit facilitated some of these transitions and resisted others.